The Effects of Telmisartan and Its Combinations on Office Blood Pressure: Results of Prospective Observational Study TAINA - O. D. Ostroumova; A. I. Kochetkov; F. T. Ageev; G. S. Anikin; E. Kh. Akhmetzyanova; E. I. Bezuglova; A. B. Bekoeva; N. Yu. Borovkova; N. G. Vinogradova; E. V. Gorbunova; A. A. Goryacheva; E. S. Zhugrova; et al. (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate the effectiveness and safety of telmisartan, used in monotherapy or in combination with hydrochlorothiazide or amlodipine, in real clinical practice in patients with diagnosed arterial hypertension who have not reached the target levels of blood pressure (BP).Material and methods. The study was a non-intervention, prospective, multicenter, comparative, observational, epidemiological program, which was carried out in Russian medical institutions. The total patient population in which the prescribed therapy was administered included 1933 people (758 men and 1175 women, mean age 57.0-59.3 years). Participants were followed-up for 12 weeks. The change in office BP was evaluated on the 4th and 12th week.Results. Significant (p<0.001 in all cases) change in office BP compared with the initial data were recorded in all study groups of therapy already at 4 weeks of treatment and became even more pronounced at 12 weeks. In the telmisartan monotherapy group, BP decreased from 155.7±10.7/92.2±7.6 mm Hg to 131.4±12.1/80.8±7.3 mm Hg at the end of the 4th week and to 125.3±7.6/78.2±6.1 mm Hg – at the end of the 12th week. Similarly, after treatment with the combination of telmisartan and hydrochlorothiazide, BP decreased from 162.7±12.6/94.3±7.9 mm Hg to 133.2±12.5/81.6±8.4 mmHg at the end of the 4th week and to 126.0±7.8/78.4±6.7 mm Hg – at the end of the 12th week. In telmisartan/amlodipine group, a decrease in BP also occurred, from 162.5±13.2/94.6±8.6 mm Hg to 132.8±14.5/81.3±7.5 mm Hg on the 4th week and to 125.4±8.7/78.4±5.6 mm Hg at the end of follow up (12 weeks). The proportion of patients who reached the target BP (<140/90 mm Hg) after treatment with telmisartan as monotherapy was 91.7%, after treatment with telmisartan+hydrochlorothiazide – 89.6%, after treatment with telmisartan+amlodipine – 92.8%. Throughout the program, prescribed therapy was well tolerated by patients. During the study, 47 adverse events (AEs) were recorded in 36 patients: 31 AEs with telmisartan monotherapy, 5 AEs with telmisartan/hydrochlorothiazide combination, and 11 AEs with telmisartan/amlodipine combination. Most of the AEs registered during the trial resolved by the end of the study, in four cases the date of AEs resolve is unknown, in two cases, at the time of completion of the study, AEs continued.Conclusion. In the TAINA study a high antihypertensive efficacy and a comparable favorable safety and tolerability profile of telmisartan, used as monotherapy and in combination with hydrochlorothiazide or amlodipine was determined.